Virtual Infrastructure: Putting Information Infrastructure on the Technology Curve - Tennenhouse, David; Lampson, Butler; Gillett, Sharon; Klein, Jennifer S. (Computer Networks and ISDN Systems, 1996)
In this paper, we offer a vision of what it would mean for the National Information Infrastructure to be a Virtual Infrastructure that takes full advantage of the digital paradigm. We begin by examining various distribution infrastructures—including those for utilities and packaged goods as well as information— and analyze differences among them and among the commodities that they distribute. We present a taxonomy of distribution models and describe the model we believe is the natural outcome. In our model, the infrastructure is not only competitive, it is also generic (can carry many types of information) and decoupled (not vertically bundled). Fundamental properties of digitized information favor this model: the ability to represent all digital information symbolically and in a fundamental unit (the bit); the ease and declining expense of switching and converting digital information; the ability to use a general-purpose, medium-independent network; and the software-based ability to defer the binding of resources until they are needed. We explore several technical issues associated with the emergence of a virtual infrastructure, including information appliances and software, the mosaic of overlapping distribution networks, and the brokerage functions that match up suppliers, distributors, and customers. Heterogeneity is a key challenge. We conclude with a discussion of the policy implications of this work, especially policies that foster innovation by making it easy to deploy new technology. We consider decoupling the regulation of information services from the regulation of information distribution, dealing with monopolies and vertical integration, and the publication of interface specifications.